Identification of Theaflavin-3,3’-Digallate as a Novel Zika Virus Protease Inhibitor - Cui, Xiangling; Zhou, Rui; Huang, Chenchao; Zhang, Rongyu; Wang, Jing; Zhang, Yongxin; Ding, Jiwei; Li, Xiaoyu; Zhou, Jinming; Cen, Shan (Frontiers in Pharmacology, 2020)
Mounting evidence indicates that Zika virus (ZIKV) is closely related to neurological disorders such as microcephaly and Guillain-Barré syndrome. There are currently no effective vaccines and FDA-approved inhibitors against ZIKV infection. The flaviviral heterodimeric serine protease NS2B-NS3 plays an essential role in ZIKV maturation and replication, thus becoming a promising target in anti-ZIKV therapy. Herein, we developed a fluorescence-based screening assay to search for inhibitors targeting the ZIKV NS2B-NS3 protease (ZIKVpro), and identified theaflavin-3,3’-digallate (ZP10), a natural active compound derived from black tea, as a potent ZIKV protease inhibitor in vitro (IC50=2.3μM). ZP10 exhibited dose-dependent inhibitory effect on ZIKV replication (EC50=7.65μM) and inhibited the cleavage of ZIKV polyprotein precursor. Moreover, ZP10 was showed to directly bind to ZIKVpro, and a docking model further revealed that ZP10 interacted with several critical residues at the proteolytic cavity of the ZIKVpro. This study highlights that ZP10 has anti-ZIKV potency through ZIKVpro inhibition, which indicates its potential application in anti-ZIKV therapy.